Mental Health, Greenness, and Nature Related Behaviors in the Adult Population of Stockholm County during COVID-19-Related Restrictions - Lõhmus, Mare (Int J Environ Res Public Health, 2021)
International data suggest that exposure to nature is beneficial for mental health and well-being. The restrictions related to the COVID-19 pandemic have created a setting that allows us to investigate the importance of greenness exposure on mental health during a period of increased isolation and worry. Based on 2060 responses from an online survey in Stockholm County, Sweden, we investigated: (1) whether the COVID-19 pandemic changed peoples’ lifestyle and nature-related habits, and (2) if peoples’ mental health differed depending on their exposure to greenness. Neighborhood greenness levels were quantified by using the average normalized difference vegetation index (NDVI) within 50 m, 100 m, 300 m, and 500 m buffers surrounding the participant’s place of residence. We found that the number of individuals that reported that they visited natural areas “often” was significantly higher during the pandemic than before the pandemic. Higher levels of greenness surrounding one’s location of residence were in general associated with higher mental health/well-being and vitality scores, and less symptoms of depression, anxiety, and perceived and cognitive stress, after adjustments for demographic variables and walkability. In conclusion, the results from the present study provided support to the suggestion that contact with nature may be important for mental health in extreme circumstances.